2016
DOI: 10.4110/in.2016.16.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis Associated with Acetaminophen Use during Viral Infections

Abstract: An association between drug treatment for viral infections and severe cutaneous adverse reactions has been noted. We investigated six patients diagnosed with Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) after being prescribed acetaminophen for suspected viral illnesses. Multiplex analysis was performed to measure cytokine levels in sera before and after treatment. IL-2Rα levels significantly decreased during the convalescence phase. Although acetaminophen is relatively safe, the drug can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…And in the present study, the time period between the intake of the causative drug and the start of skin eruption ranged from 0.5 to 13 days (median, 2.0 days), which is shorter than typically reported (1 day–1 month after drug exposure.). Similarly to the present study, SJS/TEN has been reported to develop less than or equal to week after treatment with acetaminophen . And Kaniwa et al .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…And in the present study, the time period between the intake of the causative drug and the start of skin eruption ranged from 0.5 to 13 days (median, 2.0 days), which is shorter than typically reported (1 day–1 month after drug exposure.). Similarly to the present study, SJS/TEN has been reported to develop less than or equal to week after treatment with acetaminophen . And Kaniwa et al .…”
Section: Discussionsupporting
confidence: 87%
“…It is difficult to establish which drug is specifically responsible for causing SJS/TEN. SJS/TEN has been reported to be associated with acetaminophen ingestion under viral infection . Although acetaminophen is relatively safe, it is suspected that SJS/TEN is caused by an interaction between acetaminophen and viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty case reports of SJS/TEN related to acetaminophen are available in the international literature , two of them with a positive rechallenge. We were able to apply ALDEN retrospectively using available data in 12 cases.…”
Section: Discussionmentioning
confidence: 99%